Cultural Dimensions of India–Thailand Relations: A Historical Perspective. (July 2022) - Singh, Karmveer
In today's world of 'Asianisation' whereby the countries of Asia are reinventing their historical linkages and asserting their combined power on the world stage, an understanding of the cultures of neighbours and how reciprocal cultural linkages can contribute to enhance cooperation among the countries assumes importance. India shares a long history of cultural and commercial contacts with the region of Southeast Asia including Thailand date back to the very early centuries of the Common Era, perhaps even earlier. India's interaction with this region in terms of history, culture and religion has been unique, deep, rich and apparently visible even today. Since time immemorial, the Bay of Bengal has been a highway of communication between the two regions bringing closer the cultures, economies and the people of both sides. Culture, along with commerce, contributed to exchange of ideas and knowledge between the two regions. The people of this land became so responsive to the Indian cultural elements that they imbibed and well adapted these to the native environmental conditions. Through contact and interaction, Indian cultural influence slowly and gradually penetrated into the local pattern of life in Southeast Asia. This peaceful penetration of Indian culture was carried out by traders, Brahmin priests, Buddhist monks, scholars and adventurers all along the maritime trade routes. The notable feature of this early interaction is that, the native people of Southeast Asia did not follow Indian cultural traits blindly. They absorbed only those Indian cultural elements into their indigenous cultural patterns which were either consisted with or could be shaped to their own beliefs and necessities. The process of Indian cultural influence never eradicated indigenous foundation of their society and culture. Moreover, it has been a mutual learning process in which both sides learned many things from each other. In order to understand and comprehend the processes responsible for such deep cultural interactions, Thailand has been chosen as a case study, owing to its geographical and historical proximity. India and Thailand located in each other's extended neighbourhood and share a unique cultural linkage with the great Indian Emperor Ashoka, sending Buddhist missionaries to Thailand and thus making it one of the major religions in Thailand and the rest of Southeast Asia. A notable feature of this time-honoured cultural interaction is that it has been entirely peaceful and having no political ambitions. In modern times, the civilisational linkages constitute a special asset for the further development of multifaceted relationship between the two countries. The shared cultural heritage helps both the countries to understand and confront contemporary challenges. This article attempts to study the cultural dimensions of India's multifaceted interaction with Thailand in the historical context. It argues that history and culture are central to any understanding of prospective Indo-Thai relations, and therefore, should be harnessed and promoted as a foreign policy tool to take the bilateral relations to the next level.